Jazz Chants for Children : Rhythms of American English Through Chants, Songs and Poems - Graham, Carolyn; Illustrated by Anna Veltfort (New York Oxford University Press, 1979)
A collection of chants, songs, and poems designed to teach the rhythms of spoken American English primarily to students of English as a second language.
Include Colored Illustration
Keywords: Chants -- English language--Spoken English -- English language -- Children's songs -- Jazz vocals -- Children's poetry, American -- United States -- Americanisms